(3GdHOGFY hGdCSQGQ aj MbjbI GdQO hGdGfJUGQs
(3ChdgG (B:s
(3GdMeO ddg GdYGde HNajGJ GdCSQGQ GdeWdY Ydi eG LGd ai GdNhGWQ hGdCacGQ s
(3BNQgG (B:s
(3SHMGf Gddg hHMeOg YOO Ndbg hQVi faSg hRfI YQTg MSHi Gddg hfYe Gdhcjd fYe Gdehdi hfYe GdfUjQ hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B_ (3ecfGS (B(10/ 1) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs